La Libia fascista di Federico Ravagli - Ridani, Cecilia (Italogramma, 2021)
<span dir="ltr" style="left: calc(var(--scale-factor)*56.66px); top: calc(var(--scale-factor)*197.56px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.924946);" role="presentation">The article examines the Libyan production of Federico Ravagli<span dir="ltr" style="left: calc(var(--scale-factor)*367.15px); top: calc(var(--scale-factor)*197.56px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.922918);" role="presentation">, a professor from Emilia Romagna <span dir="ltr" style="left: calc(var(--scale-factor)*56.66px); top: calc(var(--scale-factor)*211.36px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.93823);" role="presentation">who during the Fascist period moved to Libya where taught at the Italian high school in Tripoli. At <span dir="ltr" style="left: calc(var(--scale-factor)*56.66px); top: calc(var(--scale-factor)*225.19px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.907093);" role="presentation">the same time, he carried out an outstanding chronicle and documentary activity. <span dir="ltr" style="left: calc(var(--scale-factor)*56.66px); top: calc(var(--scale-factor)*238.99px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.931035);" role="presentation">Ravagli <span dir="ltr" style="left: calc(var(--scale-factor)*96.86px); top: calc(var(--scale-factor)*238.99px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.814049);" role="presentation">uses <span dir="ltr" style="left: calc(var(--scale-factor)*120.38px); top: calc(var(--scale-factor)*238.99px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.895853);" role="presentation">writing as a means of recoun<span dir="ltr" style="left: calc(var(--scale-factor)*257.81px); top: calc(var(--scale-factor)*238.99px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.923144);" role="presentation">ting his experience in the colony, which he will put later at <span dir="ltr" style="left: calc(var(--scale-factor)*56.66px); top: calc(var(--scale-factor)*252.79px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.908271);" role="presentation">the service of the propaganda of the Mussolini regime. <span dir="ltr" style="left: calc(var(--scale-factor)*56.66px); top: calc(var(--scale-factor)*266.59px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.886983);" role="presentation">In the three texts analyzed, Libya does not have the exotics features which characterized the first tales <span dir="ltr" style="left: calc(var(--scale-factor)*56.66px); top: calc(var(--scale-factor)*280.39px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.907686);" role="presentation">of travel, but it becomes the ext<span dir="ltr" style="left: calc(var(--scale-factor)*208.01px); top: calc(var(--scale-factor)*280.39px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.91133);" role="presentation">ension of Italy. The representation of “quarta sponda” that the author <span dir="ltr" style="left: calc(var(--scale-factor)*56.66px); top: calc(var(--scale-factor)*294.19px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.902451);" role="presentation">offers to us is the place where the virtues of the fascist superman are affirmed and where the cultural <span dir="ltr" style="left: calc(var(--scale-factor)*56.66px); top: calc(var(--scale-factor)*307.99px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.927417);" role="presentation">military value of Italian man in best displayed.